Peculiarities of cardiovascular remodeling in hypertensive patients at high additional risk with concomitant subclinical hypothyroidism - V. V. Syvolap; Ye. V. Novikov (Zaporožskij Medicinskij Žurnal)
Arterial hypertension affects over 12 million people in Ukraine, which accounts for about 30 % of the adult population, and is a powerful independent risk factor for cardiovascular morbidity and mortality.